Report from the 23rd International Congress of Historical Sciences Poznań 2020/2022 on 21–27 August 2022 - Filipowska, Karolina (Studia Historiae Oeconomicae, 2023)
XXIIIth International Congress of Historical Sciences 2020/2022 in Poznań.